Stock options and the strategic use of managerial incentives - Reitman, David (American Economic Review, 1993)
In Cournot-based oligopoly models there is an incentive for firms to pursue overly aggressive behavior, resulting in prices and profits below those of the Cournot equilibrium. Compensating managers in proportion to a combination of profits and sales provides one mechanism through which aggressive behavior emerges. However, when the profit component of managerial compensation comes in the form of stock options, the aggressive behavior is restrained or even eliminated in equilibrium. This result relies only on the nonlinearity of the stock option; generalizations to other forms of compensation are discussed. Copyright 1993 by American Economic Association.